2023
DOI: 10.1088/1755-1315/1215/1/012023
|View full text |Cite
|
Sign up to set email alerts
|

Production of Environmental Sensitivity Maps for Desertification in Southern Marshes of Iraq

Ahmed F. Al-Yasiry,
Alaa M. Al-Lami,
Ali Al-Maliki

Abstract: The arid and semi-arid regions have faced critical desertification problems in the last decades. This phenomenon is caused either by human actions or natural circumstances. The study aims to identify the sensitive areas of desertification in the marshlands of southern Iraq using the Environmental Sensitivity Areas Index (ESAI) for desertification. The study area is located between longitudes (46.1° to 48.1° E) and latitude (29.55° to 32.55° N), which includes parts of the governorates of Al-Amarah, Al-Basara a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Declining natural capacity of the soil to support crops or livestock due to poor irrigation practices, lack of water, overgrazing, and urbanization are causing desertification in the country [ 61 , 62 ]. Although no prior assessments on land degradation have been conducted in the study area, our findings are in line with the earlier reports indicating higher sensitivity to degradation [ [61] , [62] , [63] , [64] , [65] , [66] ]. Reforestation, agricultural area rehabilitation, teamwork, and cutting-edge biotechnological techniques are essential to lessen the negative effects of desertification on communities, economies, ecosystems, and human health.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Declining natural capacity of the soil to support crops or livestock due to poor irrigation practices, lack of water, overgrazing, and urbanization are causing desertification in the country [ 61 , 62 ]. Although no prior assessments on land degradation have been conducted in the study area, our findings are in line with the earlier reports indicating higher sensitivity to degradation [ [61] , [62] , [63] , [64] , [65] , [66] ]. Reforestation, agricultural area rehabilitation, teamwork, and cutting-edge biotechnological techniques are essential to lessen the negative effects of desertification on communities, economies, ecosystems, and human health.…”
Section: Resultssupporting
confidence: 93%
“…Land degradation and desertification are major issues in Iraq that are largely caused by human activity and climate change [ [61] , [62] , [63] , [64] , [65] , [66] ]. The semi-arid environment, low rainfall, and high evaporation rates in the country are contributing to the increased desertification (39% of the country's area).…”
Section: Resultsmentioning
confidence: 99%
“…The results indicated a significant decrease in vegetation cover in both regions (Bakr et al, 2024). Many studies have evaluated the impact of the decreasing precipitation levels during the last decades on the hydrological situation in different regions of Iraq, especially in the marshes area of southern Iraq, and the results revealed that more than 90% of this area are sensitive to desertification (Al-Yasiry et al, 2023).…”
Section: Fig 6: Slope Values For M-k Test (Z) For All Stations Of Iraqmentioning
confidence: 95%